Evaluating the Health System Responsiveness after the Implementation of the Health System Transformation Plan in Zahedan - Fatemeh Setoodehzadeh; Milad Nasaji; Najmeh Azizi; Mostafa Peyvand (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: The World Health Organization defines responsiveness as the ability of a health sys tem to respond to the reques ts and needs of individuals in non-clinical but logical cases that s trengthen the health sys tem. This s tudy aimed to evaluate the responsiveness of the health sys tem after the implementation of the health sys tem transformation plan. Methods: This descriptive-analytical s tudy was performed on 310 households in 2019 in Zahedan, Iran. Data were collected by clus ter sampling method. In this s tudy, the World Health Organization Ques tionnaire was used. Ques tionnaires were completed by interviewing the head of the household. Data were analyzed using SPSS-v22. Results: Regarding outpatient services, the highes t percentage of good performance belonged to the respect for people's dignity dimension (45%), the highes t percentage of average performance belonged to the dimensions of quality of basic amenities (55%), and the highes t percentage of poor performance was in the dimension of freedom of choice (40%). In inpatient services, the highes t good performance belonged to the respect for people's dignity dimension (35%), the highes t average performance belonged to the clarity of communication dimension (48%), and prompt attention, social support, and confidentiality (45%). Conclusion: In this s tudy, it was found that "prompt attention" and "respect for people's dignity" were the mos t important and "the freedom of choice" was the leas t satisfied, and this low level of satisfaction could be due to the lack of expert and efficient s taff in the field of meeting the needs of the society in the city of Zahedan. Therefore, the university should try to train specialized and efficient s taff.